Non-automotive manufacturing in the Eastern Cape: a study of the sector's decline and possible policy solutions - Martin, Lucy (School of Economics, 2014)
The automotive and automotive components industry has long formed the backbone of manufacturing in the Eastern Cape. Supported by the Motor Industry Development Programme (MIDP) since 1995, the sector has been a major source of industrial growth and employment creation in the province. In contrast, the province's non-automotive manufacturing (NAM) firms, the vast majority of which were attracted to the area by generous apartheid-era incentive schemes in the 1970s and 1980s, are struggling to maintain output and employment in the absence of government support. Since the withdrawal of incentives in 1992, non-automotive subsectors have experienced a contraction in output and employment, few new entrants, little innovation, and a substantial amount of firm closures. This thesis aims to identify the current constraints facing non-automotive manufacturing firms in the Eastern Cape. Its findings are based on interviews conducted in September and October 2013. 25 firms and 7 key industry representatives were interviewed in the metros and surrounding industrial areas of East London and Port Elizabeth. Interviews were structured loosely around a questionnaire that focused on eight identified constraining factors. The interview process was conversational, aimed at engaging in a meaningful dialogue with firms and industry representatives. The secondary aim of this thesis is to utilise the information obtained through firm interviews to provide possible targeted policy solutions to address the constraints facing non-automotive manufacturing subsectors in the Eastern Cape. In light of the Eastern Cape Provincial Industrial Development Strategy's (PIDS) scheduled revision in 2015, this thesis makes the case for (1) placing a larger emphasis on regionally and sectorally specific industry policies within the new PIDS;; and (2) increasing engagement with the private sector in order to better inform the policymaking process.